(3QSGdI aj CfSGH GdbHGFd GdJj ScfJ eOjfI RHjO HGdjefs - (3eMeO Hf Ydj, LeGd GdOjf GdbQTj GdoenOrgpLf,J (B895 (3g` s
(3ChdgG (B:s
(3heeG hLO HNW eDdag fGbGO Yf GdgeOGfj Cgd eOjfI RHjO gi ddCTYQjjf s
(3BNQgG (B:s
(3hHfi Nda ef Hfi dGe hHfi Gdeci ef bQjT s
(3Vef eLehY , JQJjHgG (B: (3ef U (B102 - (3U(B103s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B289 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B62s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B197 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs